The Crime of Child Abduction According to Law 20-15 - Cherdoud, Tayeb (Journal of Legal Studies and Researches, 2024)
This article aims to explain what happened in the crime of kidnapping children under law 20-15, which only touched the crime of kidnapping children through violence, threats, luring, or other means, whether with regard to follow-up and the criminal penalty for it. This article concludes with a set of results. That have been reached and some suggestions that we see as complementary to what the legislator came up with.